A Comparison of Endoscopic Retrograde Pancreatography With or Without Pancreatoscopy for Removal of Pancreatic Duct Stones. Issue 5 (May 2019) - Han, Samuel; Shah, Raj J.; Brauer, Brian C.; Edmundowicz, Steven A.; Hammad, Hazem T.; Wagh, Mihir S.; Wani, Sachin; Attwell, Augustin R.
Abstract : Objectives: Pancreatic duct stones contribute to pain in patients with chronic pancreatitis, and per-oral pancreatoscopy (POP) allows visualization, fragmentation, and removal of these stones. This study compared the safety and efficacy of endoscopic retrograde pancreatography (ERP) with and without POP. Methods: This single-center retrospective review compared ERP with and without POP for treatment of main-duct pancreatic duct stones. The primary outcome was technical success, defined as partial or complete stone removal, which was compared between the 2 groups. Results: In all, 223 patients underwent 549 ERPs with a technical success rate of 92.4% and complete stone clearance rate of 74.9%. Patients undergoing ERP with POP (n = 94) had higher technical success than patients undergoing ERP without POP (n = 129, 98.9% vs 87.6%, P < 0.001), but required more ERPs (3.1 vs 1.9, P = 0.02). Endoscopic retrograde pancreatography with POP was associated with larger stone size (8.9 vs 6.1 mm, P = 0.001), more stones per case (5+ stones: 33.8% vs 21.1%, P = 0.002), and more impacted stones (48.8% vs 10.3%, P < 0.001). Conclusions: Per-oral pancreatoscopy–guided lithotripsy permits effective stone removal in cases not amenable to standard ERP techniques, including those with larger or more numerous stones. Abstract : Supplemental digital content is available in the text.